Pre-clinical to Clinical Translational Failures and Current Status of Clinical Trials in Stroke Therapy: A Brief Review - Dhir, Neha; Medhi, Bikash; Prakash, Ajay; Goyal, Manoj K.; Modi, Manish; Mohindra, Sandeep (Current Neuropharmacology, 2020)
In stroke (cerebral ischemia), despite continuous efforts both at the experimental and clinical level, the only approved pharmacological treatment has been restricted to tissue plasminogen activator (tPA). Stroke is the leading cause of functional disability and mortality throughout worldwide. Its pathophysiology starts with energy pump failure, followed by complex signaling cascade that ultimately ends in neuronal cell death. Ischemic cascade involves excessive glutamate release followed by raised intracellular sodium and calcium influx along with free radicals’ generation, activation of inflammatory cytokines, NO synthases, lipases, endonucleases and other apoptotic pathways leading to cell edema and death. At the pre-clinical stage, several agents have been tried and proven as an effective neuroprotectant in animal models of ischemia. However, these agents failed to show convincing results in terms of efficacy and safety when the trials were conducted in humans following stroke. This article highlights the various agents which have been tried in the past but failed to translate into stroke therapy along with key points that are responsible for the lagging of experimental success to translational failure in stroke treatment.
Keywords: Stroke